Pemberdayaan Masyarakat Desa Benelan Lor Bersama BUMDes Melalui Budidaya Maggot BSF Demi Mendukung Program Desa Bersih - Rusadi, Tri Maryono; Hardiyanti, Siska Aprilia; Ton, Sefri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Waste is a problem faced by all countries around the world, including Indonesia. The increasing amount of waste is due to ineffective management. However, some villages in Banyuwangi, including Benelan Lor, are starting to make efforts to manage waste more effectively. Given the rising volume of organic waste generated by the community and its impact on the environment, proper processing is essential, one of which is maggot farming. One challenge faced by partners is the lack of community awareness regarding household waste management. Therefore, raising awareness about effective waste management is crucial, as it can also provide income opportunities for the community. One solution that can be implemented is the farming of Black Soldier Fly (BSF). This initiative begins with surveys, the construction of breeding facilities, and socialization and training on BSF farming. It is hoped that through this activity, partners will be able to manage waste independently and support the economic improvement of the community in Benelan Lor Village.